ACTION OF AVAPEEDAKA SNEHA ON MUTRA VEGADHARANA JANYA LAKSHANAS- A REVIEW - Rini P; Rekha B.V; Venkatakrishna K.V (International Journal of Applied Ayurved Research, 2021)
Introduction: The homeostasis of the human body is maintained by all the metabolic activi-ties happening inside & all the toxic products of these are mainly excreted through Mutra(Urine), Purisha(Feaces) & Sweda(Sweat). Among which Mutra is very much im-portant because it has got additional functions like regulation of blood pressure etc. The effect of suppression of urine is found to be mainly painful conditions & this pain is caused mainly because of nervous irritation & stretching of muscles. Avapeedaka Sneha (A special type of oral administration of lipid) which is given as Pragbhakta(Before food) & Jeernantika (After digestion of food) is found effective in such condition. This sneha given less importance in regular practice & different methods of practice are adopted .So there is a need of literature review in depth. Aims & objectives: Reviewing the scattered information regarding Avapeedaka sneha and its applicability in symptoms of suppression of urine. Methods: liter-ature review Discussion: The study tries to reveal the effect of Avapeedaka Sneha in Mutra Vegadharana (suppression of urine) symptoms. Conclusion: Mutravegadharana is common now a day due to busy lifestyle and one can adopt Avapeedaka Snehapana as both preventive and curative aspect.